2018
DOI: 10.1016/j.cjca.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

2018 Canadian Cardiovascular Society/Canadian Association of Interventional Cardiology Focused Update of the Guidelines for the Use of Antiplatelet Therapy

Abstract: Antiplatelet therapy (APT) has become an important tool in the treatment and prevention of atherosclerotic events, particularly those associated with coronary artery disease. A large evidence base has evolved regarding the relationship between APT prescription in various clinical contexts and risk/benefit relationships. The Guidelines Committee of the Canadian Cardiovascular Society and Canadian Association of Interventional Cardiology publishes regular updates of its recommendations, taking into consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
251
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(258 citation statements)
references
References 132 publications
6
251
0
1
Order By: Relevance
“…[13][14][15] Major international guidelines also recommend initiation of at least 12 months of dual antiplatelet therapy (DAPT) with aspirin and a P2Y 12 inhibitor (ticagrelor, prasugrel, or clopidogrel) in patients with NSTEMI who are managed with medical therapy and/or who are treated with revascularization (ie, irrespective of initial treatment strategy), unless there are previous or ongoing contraindications. [13][14][15][16][17][18] Ticagrelor is recommended over clopidogrel for patients with NSTEMI, including those pretreated with clopidogrel (which should be discontinued when ticagrelor is started). Ticagrelor is contraindicated in patients with previous intracranial hemorrhage or ongoing bleeds.…”
Section: Guideline Recommendations For Invasive and Antiplatelet Trmentioning
confidence: 99%
“…[13][14][15] Major international guidelines also recommend initiation of at least 12 months of dual antiplatelet therapy (DAPT) with aspirin and a P2Y 12 inhibitor (ticagrelor, prasugrel, or clopidogrel) in patients with NSTEMI who are managed with medical therapy and/or who are treated with revascularization (ie, irrespective of initial treatment strategy), unless there are previous or ongoing contraindications. [13][14][15][16][17][18] Ticagrelor is recommended over clopidogrel for patients with NSTEMI, including those pretreated with clopidogrel (which should be discontinued when ticagrelor is started). Ticagrelor is contraindicated in patients with previous intracranial hemorrhage or ongoing bleeds.…”
Section: Guideline Recommendations For Invasive and Antiplatelet Trmentioning
confidence: 99%
“…10,11 A shift to dual pathway antithrombotic management is also advocated in the 2018 updates of the CCS antiplatelet and atrial fibrillation guidelines. 16,17 The recently published AUGUSTUS trial (apixaban), that also included medically managed ACS patients, also supports the safety advantage of dual pathway therapy over triple therapy. 12 The ENTRUST-PCI AF trial (edoxaban) furtherly reinforced the safety and anti-ischemic efficacy of dual pathway regimens of dual pathway over triple therapy, with no significant difference in ischemic events between the two groups.…”
Section: Resultsmentioning
confidence: 89%
“…The emergence of dual pathway antithrombotic therapy (anticoagulant plus a single antiplatelet agent) in clinical practice, on the other hand, represents an integration of randomized trial data from PIONEER AF‐PCI (rivaroxaban) and REDUAL (dabigatran) that showed that such a regimen could minimize bleeding risk without a signal for increase in clinical ischemic events . A shift to dual pathway antithrombotic management is also advocated in the 2018 updates of the CCS antiplatelet and atrial fibrillation guidelines . The recently published AUGUSTUS trial (apixaban), that also included medically managed ACS patients, also supports the safety advantage of dual pathway therapy over triple therapy .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations